Analisis Penerapan Sanksi Pidana Analisis Penerapan Sanksi Pidana Pelaku Residivis Tindak Pidana Narkotika: Tindak Pidana Narkotika, Analisis, Residivis - Benny Irawan; Hizkia Raymond (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2021)
Abstract In positive law, narcotics crimes are qualified as extraordinary crimes, because the impact of these crimes has a dangerous situation that is widespread. Law No. 35 of 2009 is the basic rule for law enforcement officers to carry out law enforcement for perpetrators. In Article 54 of the Law it is explained that judges are obliged to consider conducting medical rehabilitation for drug users. In Decision No. 745/Pid. Sus/2018/PN Srg, the defendant is a drug case recidivist who had previously been rehabilitated. By using a normative juridical research method that uses the approach of legislation and legal principles, this study aims to examine and determine the application of punishment to recidives in Decision No. 745/Pid. Sus/2018/PN Srg by using the theory of judges' considerations and the purpose of sentencing. The results of this study are the application of sanctions against narcotics crime recidivists must use the purpose of punishment which results in a deterrent effect for the perpetrator, so that the perpetrator does not repeat the action.